Defining identity and the changing scope of culture in the digital age - Novak, Alison; El-Burki, Imaani Jamillah, 1981-; IGI eBooks; IGI Global (Hershey, Pennsylvania (701 E. Chocolate Avenue, Hershey, PA 17033, USA) : IGI Global, 2016)
"This book explores a multitude of topics pertaining to self-hood, self-expression, human interaction, and perceptions of civilization and culture in an age where technology has become integrated into every facet of our everyday lives"--Provided by publisher.
Living parallel-ly in real and virtual: internet as an extension of self / Jannatul Akmam, Nafisa Huq -- The self of the camera: popular practices of photography and self-presentation in the new social media / Gilbert Ndi Shang -- The electric soul: faith, spirituality, and ontology in a digital age / Benjamin J. Cline.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed 06/04/2016).
Keywords: Information technology -- Social aspects; Technological innovations -- Social aspects; Identity (Psychology); Social change; Computer-mediated communications; Digital culture; Digital identity; Digital natives; Gender and diversity; Online communities; Social media; Electronic books